Modern Societies and the Science of Religions: : Studies in Honour of Lammert Leertouwer - Leertouwer, Lammert.; Wiegers, Gerard Albert, 1959-; Platvoet, Jan. (Numen Book Series, 2002)
This book brings together studies by seventeen specialists in the science of religions in which they relate the changes in their discipline to the changes which have occurred in a select number of modern(ising) societies worldwide. It attempts to study these developments in their relation to and as conditioned and constrained by cultural change, changes in educational systems, technology, population (for example migration), economic patterns, politics, and, last but not least, religious systems. The essays focus on resp. France, Germany, the Netherlands, Spain, the USA, Turkey, Israel, Morocco, Saudi Arabia, South Africa, Indonesia, Japan, and China. Written in honour of Dr. Lammert Leertouwer, professor of History of Religions and the Comparative Study of Religions at Leiden University from 1979 until his retirement in 1997, the book is particularly important for all those who are interested in the religious, social and political contexts of the academic Study of Religions in general and in the various countries dealt with in particular.